THE ROLE OF EDUCATION IN THE INTEGRATION PROCESS OF FORCED MIGRANTS - Bereznaja-Demidenko, Valentina; Štuopytė, Edita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article deals with educational factors that involve the integration process of forced migrants. Non-formal training of multicultural communication skills is analysing as one of several educational factor of forced migrants’ integration. Moreover there is analyzed how non-formal training activities influence the emotional state and abilities of forced migrants’ minors. These results are relevant for institutions and communities that face with the multicultural communication every day. The theoretical parts of article contain the analysis of the publications made on the integration of forced migrants and multicultural communication in the integration process of the review. The empirical part of the research present how non-formal training activities influence on minors forced migrants emotional state and their preparation to the integration.